2015
DOI: 10.1049/el.2015.2074
|View full text |Cite
|
Sign up to set email alerts
|

Random telegraph signals originating from unrelaxed neutral oxygen vacancy centres in SiO 2

Abstract: Unrelaxed neutral oxygen deficiency centres (ODCs) (V 0 ODC II) in SiO 2 have been identified as the cause of random telegraph signals (RTSs) in highly scaled n-type metal-oxide-semiconductor fieldeffect transistors. Variable temperature RTS measurements were performed to extract trap capture cross-sections, capture activation energy, relaxation energy associated with the gate oxide defects, and the trap energy in the SiO 2 bandgap to determine the trap species and type. The results indicate that the electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In an earlier publication [27], we demonstrated that these E R and E B values are indicative of unrelaxed neutral oxygen deficiency centers (V 0 ODC II) that become repulsive centers upon capturing an electron (Fig. 6) [17], [27], [44], [45].…”
Section: Rts Model Verificationmentioning
confidence: 65%
See 4 more Smart Citations
“…In an earlier publication [27], we demonstrated that these E R and E B values are indicative of unrelaxed neutral oxygen deficiency centers (V 0 ODC II) that become repulsive centers upon capturing an electron (Fig. 6) [17], [27], [44], [45].…”
Section: Rts Model Verificationmentioning
confidence: 65%
“…3. In general, average times associated with the traps located further deep in the oxide bulk show stronger dependence on V GS than those associated with the traps closer to the Si/SiO 2 interface [27], [42].…”
Section: Rts Model Verificationmentioning
confidence: 90%
See 3 more Smart Citations